Perilaku pemeliharaan kebersihan gigi tiruan lepasan pada masyarakat Desa Kema II Kecamatan Kema - Kaliey, Inda P.; Wowor, Vonny N. S.; Lampus, Benedictus S. (e-GiGi, 2016)
Abstract: The main purpose of using denture is to restore the aesthetic function, speech function, and masticatory function which are disturbed due to tooth loss. Unclean oral condition can cause the oral cavity become susceptible to caries and periodontal disease. Poor behavior to maintain dental and oral hygiene of removable denture users plays an important role in the occurrence of these two diseases. Removable denture that is kept unclean is harmful to the hard tissue as well as the soft tissue of the oral cavity. This study aimed to determine the behavior of removable denture maintenance among Kema II villagers in Kema. This was a descriptive study with a cross sectional design. There were 62 respondents as samples. The results of the behavior score of denture hygiene maintenance were as follows: score of knowledge was 552; score of attitude was 581; and score of action was 572. Conclusion: The behavior to maintain the removable denture hygiene of Kema II villagers which included knowledge, attitude, and action was classified as poor category.Keywords: behavior, maintenance of hygiene dentures, removable dentureAbstrak: Tujuan utama penggunaan gigi tiruan yaitu untuk memulihkan fungsi estetik, fungsi bicara, serta fungsi pengunyahan yang terganggu akibat kehilangan gigi. Kondisi rongga mulut yang kurang terjaga kebersihannya dapat menyebabkan rongga mulut rentan terhadap karies dan penyakit periodontal. Perilaku pemeliharaan kebersihan gigi dan mulut yang kurang baik dari pengguna gigi tiruan lepasan berperan penting pada terjadinya kedua penyakit tersebut. Gigi tiruan lepasan yang kurang terjaga kebersihannya bukan saja menimbulkan gangguan pada jaringan keras gigi namun juga pada jaringan lunak mulut. Penelitian ini bertujuan untuk mengetahui perilaku pemeliharaan kebersihan gigi tiruan lepasan pada masyarakat Desa Kema II Kecamatan Kema. Jenis penelitian ialah deskriptif dengan desain potong lintang. Sampel berjumlah 62 responden. Hasil penelitian menunjukkan skor pengukuran perilaku pemeliharaan kebersihan gigi tiruan yang terdiri dari skor pengetahuan sebesar 552; skor sikap sebesar 581; dan skor tindakan sebesar 572. Simpulan: Perilaku pemeliharaan kebersihan gigi tiruan lepasan masyarakat Desa Kema II Kecamatan Kema yang meliputi pengetahuan, sikap dan tindakan kesemuanya tergolong kurang baik.Kata kunci: perilaku, pemeliharaan kebersihan gigi tiruan, gigi tiruan lepasan